Relationship between demographic characteristics and length of illness with adherence of Dm Type Ii patients controlling blood sugar levels at Rsud Rupit, Muratara Regency, 2023 - Astuti, Arni Afni; Samidah, Ida; Rustandi, Handi (Student Scientific Journal, 2024)
Diabetes mellitus (DM) is often called the silent killer because this disease can affect all organs of the body and cause several kinds of complaints. The number of people with Diabetes Mellitus (DM) based on the province in South Sumatra is 5,220 people. The region with the most sufferers is Lubuk Linggau City with 1,176 DM sufferers. The purpose of this study was to analyze the characteristics and length of illness with the compliance of respondents to control blood sugar levels at Rupit Hospital, Muratara Regency. This type of research uses analytic observations with cross sectional methods. The sample in this study were type 2 DM patients as many as 42 samples. The sampling technique was carried out by purposive sampling, the researcher conducted an interview with the help of a questionnaire instrument. The dependent variable in this study was compliance with blood sugar control, while the independent variables were characteristics and length of illness. Data analysis using the Chi Square test. The results of the study showed that there was a relationship between age and education with respondents' compliance with controlling blood sugar levels (p = 0.000) and there was no relationship between work and length of illness with compliance with controlling blood sugar levels (p> 0.005). Based on this analysis, it can be concluded that there is a relationship between age and education with respondents' compliance in controlling blood sugar levels, and there is no relationship between work and length of illness with respondents' compliance in controlling blood sugar levels. The research suggestion is for the hospital to increase knowledge and information to patients with type 2 DM about the dangers posed by diabetes mellitus in the form of complications and how to handle them.